The Implementation of Product Quality, Pricing Strategy, and Strategic Location on Purchasing Intention at Matahari Department Store Metropolitan Mall in Bekasi - Rahmat Pramukti; Yayan Hendayana; Andrian (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of product quality, pricing strategy and strategic location on purchasing intention at Matahari Department Store Metropolitan Mall Bekasi. This type of research is quantitative. The population in this study amounted to 85 people. Sampling technique using saturated sampling technique. The sample in this study amounted to 85 respondents. Data collection techniques by distributing questionnaires through Google Form. Hypothesis testing in this study using Multiple Linear Regression Analysis. The research subjects are consumers of this Department Store. The results of this study indicate that the independent variables of product quality, pricing strategy and strategic location have a significant effect on dependent variable of purchasing intention (Y).